2013
DOI: 10.1016/j.tiv.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide TEMPO: A genotoxic and oxidative stress inducer in cultured cells

Abstract: Abstract2,2,6,6-Tetramethylpiperidine-1-oxyl (TEMPO) is a low molecular weight nitroxide and stable free radical. In this study, we investigated the cytotoxicity and genotoxicity of TEMPO in mammalian cells using the mouse lymphoma assay (MLA) and in vitro micronucleus assay. In the absence of metabolic activation (S9), 3 mM TEMPO produced significant cytotoxicity and marginal mutagenicity in the MLA; in the presence of S9, treatment of mouse lymphoma cells with 1-2 mM TEMPO resulted in dose-dependent decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Nitroxides have a single unpaired electron delocalized between a nitrogen and an oxygen, and their important biological activities have been recognized for decades (Gallez et al 2004; Guo et al 2013). Piperidine nitroxides, a class of stable organic free radicals of low molecular weight, are lipophilic and permeable through cell membranes (Soule et al 2007a; Wilcox and Pearlman 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitroxides have a single unpaired electron delocalized between a nitrogen and an oxygen, and their important biological activities have been recognized for decades (Gallez et al 2004; Guo et al 2013). Piperidine nitroxides, a class of stable organic free radicals of low molecular weight, are lipophilic and permeable through cell membranes (Soule et al 2007a; Wilcox and Pearlman 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), one of the frequently used piperidine nitroxide catalysts, resulted in intercellular reactive oxygen species (ROS) generation and DNA damage in mammalian cells (Guo et al 2015). Furthermore, TEMPO and several of its derivatives induced genotoxicity in the Ames test, the mouse lymphoma assay, and the in vitro micronucleus assay (Gallez et al 1992; Guo et al 2013; Sies and Mehlhorn 1986). One TEMPO derivative, 4-methoxy-TEMPO, is commonly employed for oxidation of alcohols, as well as in synthesis of 2-substituted benzoxazoles that are widely used as antibacterial, antifungal, antimicrobial, anti-proliferative, and antiviral agents (Chen et al 2008; Demmer and Bunch 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude product contained approximately 5000 ppm TEMPO, which was unacceptably high since in vitro 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 33 results suggest that TEMPO is genotoxic in mammalian cells. 15 A study was carried out where a number of solvent systems were screened to determine whether solid 1 could be obtained. A solvent mixture of MTBE/heptane precipitated 1 out of solution containing 300 ppm of residual TEMPO.…”
Section: Final Form Determinationmentioning
confidence: 99%
“…[6] Just like their inorganic congener -nitric oxide [7] -nitroxyl radicals at submillimolar concentrations exhibit antioxidant and cytoprotective properties, [8,9] but at concentrations ≥10 À3 M, they increase oxidative stress and exert a cytotoxic effect on tumor cells. [10][11][12] Analogously to other redox active agents, [13] nitroxyl radicals modulate the activity of clinically used anticancer drugs and may improve their chemotherapeutic properties. [14][15][16] For effective use of nitroxyl radicals in such applications, it is important to know the redox and acid-base characteristics of a wide variety of structures 1-2-3.…”
Section: Introductionmentioning
confidence: 99%